Amine functionalized magnetic nano-composite materials for the removal of selected endocrine disrupting compounds and its mechanism study. Issue 4 (August 2020) - Kittappa, Shanmuga; Jang, Min; Ramalingam, Malarvili; Ibrahim, Shaliza
Graphical abstract: Highlights: MNCMT was successfully synthesized using magnetite, silica dioxide and Tris. MCNMT adsorbed different types of endocrine disrupting compound. MNCMT is economical and can be reused and recycled. Removal mechanism of EDCs was deduced using isotherm and kinetic models. The adsorbent MNCMT is suitable for larger scale application of waste water treatment. Abstract: A novel adsorbent successfully synthesized using recyclable silica, nano magnetite and N1-(3 trimethoxisilylpropyl) diethylenetriamine (TRIS) denoted as MNCMT. Three endocrine disrupting compounds (EDCs) such as bisphenol A (BPA), ibuprofen (IBP) and clorofibric acid (CFA) were selected as model drugs for this study. The sorption capacities of EDCs by MNCMT were found to be 182.6 mg g −1 for BPA, followed by CFA at 101.8 mg g −1 and 72.6 mg g −1 for IBP. The removal process matched with Langmuir isotherm and pseudo second order kinetic models with determination coefficient (R 2 ) above 0.99. The adsorbent was regenerated, recovered and reused for multiple cycles of adsorption. The physical-chemical properties and experimental data revealed that the chemical sorption is more dominant than physical sorption. Hydrogen bonding, π-π and electrostatic attractions provide intrinsic information on the removal mechanism.